Trade circuits on the Tacna-Arica axis during the early Peruvian Republic, 1840-1863. An approach to intermediate traders - Rosenblitt, Jaime (2018)
The operation of large trade circuits requires smaller-scale merchants to bring the products they control to consumers or to intervene in some of the stages of extraction and export of raw materials. The Tacna-Arica region is a good example of how both activity levels complement each other. Therefore, through specific cases, this article seeks to establish what were the alternatives available to medium-sized merchants of Tacna and Arica to develop their business and what were the circumstances that conditioned the success or failure of their activities.